Establishment of an effective endomycorrhizal association on cassava in flowing solution culture and its effects on phosphorus nutrition - Howeler, Reinhardt H.; Asher, CJ; Edwards, D.G. (Wiley, 1982)
Eight cassava (Manihot esculenta) cultivars were grown with or without mycorrhizal inoculation in flowing solution cultures containing approximately 0.1, 1, 10 or 100 ?M phosphate. Rice (Oryza sativa), maize (Zea mays), cowpea (Vigna unguiculata) and French bean (Phaseolus vulgaris) were included in the experiment for comparative purposes.